Exposure to Leishmania spp. and sand flies in domestic animals in northwestern Ethiopia - Rohousova, Iva; Talmi-Frank, Dalit; Kostalova, Tatiana; Polanska, Nikola; Lestinova, Tereza; Kassahun, Aysheshm; Yasur-Landau, Daniel; Maia, Carla; King, Roni; Votypka, Jan; Jaffe, Charles L; Warburg, Alon; et al. (Parasites & vectors, 2015)
BACKGROUND: Human visceral leishmaniasis caused by Leishmania donovani is considered an anthroponosis; however, Leishmania-infected animals have been increasingly reported in L. donovani foci, and the role of these animals as reservoirs for human L. donovani infection remains unclear. METHODS: We conducted a study of domestic animals (goats, sheep, cows, dogs, and donkeys) in three L. donovani foci in northwestern Ethiopia. Domestic animals were screened for Leishmania DNA and for anti-L. donovani IgG. Serum anti-sand fly saliva antibodies were used as a marker of exposure to the vector sand fly, Phlebotomus orientalis. RESULTS: Of 546 animals tested, 32 (5.9%) were positive for Leishmania DNA, with positive animals identified among all species studied. Sequencing indicated that the animals were infected with parasites of the L. donovani complex but could not distinguish between L. infantum and L. donovani. A total of 18.9% of the animals were seropositive for anti-L. donovani IgG, and 23.1% of the animals were seropositive for anti-P. orientalis saliva IgG, with the highest seroprevalence observed in dogs and sheep. A positive correlation was found between anti-P. orientalis saliva and anti-L. donovani IgGs in cows, goats, and sheep. CONCLUSIONS: The detection of L. donovani complex DNA in the blood of domestic animals, the reported seroprevalence to the L. donovani antigen, and the widespread exposure to sand fly saliva among domestic animals indicate that they are frequently exposed to Leishmania infection and are likely to participate in the epidemiology of Leishmania infection, either as potential blood sources for sand flies or possibly as parasite hosts.
Keywords: Cattle; protilátky protozoální; Psychodidae; Male; Etiopie; Dogs; skot; Ethiopia; Leishmaniasis; Antibodies, Protozoan; mužské pohlaví; ovce; hmyz - vektory; Sheep; Animals; Equidae; hospodářská zvířata; ženské pohlaví; Leishmania donovani; Animals, Domestic; zvířata; Insect Vectors; psi; leishmanióza; Female